Enhancing OSH Management Based on Risk Perception of Unsafe Behavior Among Infrastructure Construction Workers - Arifai, Achmad Muhyidin; Fitrina , Rehani; Adenan (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
The construction sector faces significant occupational safety challenges due to its high-risk nature. This study examines unsafe behavior among construction workers at the Sultan Hasanuddin International Airport Main Terminal project in Makassar. It aims to identify key risk factors and their impact on worker safety. Data were collected from 99 respondents, including 96 workers and three project managers, through questionnaires, interviews, and observations. Using Exploratory Factor Analysis, seven major contributors to unsafe behavior were identified: Neglecting Fundamental Occupational Safety, Breach of Cautionary Signals and Safety Protocols, Careless Behavior and Work Inaccuracies, Performing Dangerous Work Without Proper Training, Neglecting Traffic Safety in Work Zones, Neglecting Equipment Safety and Maintenance, and Unsafe Operation of Machinery and Vehicles. The findings also reveal a significant difference in risk perception between field workers and managerial staff, with field workers showing a substantially lower awareness of risks associated with unsafe behaviors. These results highlight the need for targeted training, stricter safety enforcement, better equipment maintenance, and fostering a strong safety culture through leadership commitment and continuous communication.